Accounting Information System Management, Business Processes, and The Quality of Financial Reports Mechanism - Ayu Almas Assyarofi; Luluk Muhimatul Ifada (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
ntroduction/Main Objectives: This research aims to determine and analyze the influence ofbusiness processes on the quality of financial reports. Background Problems: Business processeson the quality of financial reports were done through the mediation of the Accounting InformationSystem (AIS). Research Methods: The data used in this study were primary data obtained from theresponses of respondents to questionnaires sent to managers and accounting and finance staff invocational education in Tegal. The data analysis method used was descriptive verification with aquantitative approach. Data were processed using SmartPLS software version 4.0.9.5.Finding/Results: The study's results indicated that business processes had a significant favourableinfluence on AIS management. AIS management had a significant favourable influence on the qualityof financial reports, while business processes had a direct, significant favourable influence on thequality of financial reports. Conclusion: AIS had been proven to mediate the influence of businessprocesses on the quality of financial reports